Examining tourism stakeholder networks and relationship quality: the specific case of Peneda Gerês National Park (PNPG) - Nogueira, Sónia Fernanda Moreira (2014)
This paper draws insights from three key strategic management theories: the stakeholder theory, the network theory and the relationship quality theory. It examines how viable tourism policies could best be developed in PGNP, considering the stakeholder networks related to tourism, specifically by considering the relationship quality (trust, commitment and cooperation). Under this view it addresses the structure, nature and composition of ties among PNPG stakeholders using social network analysis (SNA) methodology, combining qualitative and quantitative techniques. Additionally, the study categorizes stakeholders according to the "stakeholder salience" model, illustrates the relationship quality among the network and stakeholder's positioning in a complex structure of relationships informing about interactions, providing possible directions to minimize potential constraints in networks.